Pengaruh Keselamatan Dan Kesehatan Kerja Terhadap Produktivitas Kerja Karyawan Bagian Produksi Ptpn Xi Pg Asembagus Kabupaten Situbondo - Ratih Puspitorini Y. A.; Dewi Kurniawati; Ahmad Zakariyah (Jurnal Ilmiah Inovasi, 2017)
Employees are a mover of company’s operating system. Work safety and work healthy factors are affect in giving a sense of security and comfort to our employees in doing their jobs. This research was conducted on employees of theProduction PTPN XI PG Asembagus Situbondo. In this research, the variables used are Work Safety (X1), Work Healthy (X2) and the Work Productivity (Y). The purpose of this research was to analyze the influence of the independent variables simultaneously and partially to the Work Productivity of employees. The analysis technique used in this research is multiple linear regression including the coefficient of determination, F test and t test. The results of this study show that: 1) Variable Work Safety (X1) and Work Healthy (X2) effect simultaneously to the Work Productivity (Y) production employees of PTPN XI PG Asembagus, 2) Variable Work Safety (X1) had no significant effect the Work productivity (Y) production employees of PTPN XI PG Asembagus, 3) Variable Work Healthy (X2) has a significant influence on the Work Productivity (Y) production employees of PTPN XI PG Asembagus.